Connection of the RES-based Power Plants into the Electric Grid - Kepalas, V.; Ramonas, Č.; Adomavičius, V. (Elektronika ir Elektrotechnika, 2007)
Problems caused by the connection of wind turbines into electric grid are discussed. Little by little number of grid-connected wind turbines in Lithuania is increasing and already makes up over 10 MW. Connection of wind turbines into electric grid causes side effects – harmonic distortion, low frequency fluctuations of voltage and flicker emissions. Paper describes flicker emissions caused by the switching operations of wind turbines and their dependence on the number of wind turbine at the site, as well as on rated power of wind turbines and other parameters. The ways for reducing impact of the mentioned side effects into quality of grid power are discussed too. Energy conversion diagram for integration of WT into electric grid is presented. The diagram has rectifier of generator’s current, short-circuiter and inverter in wind turbine’s power conversion chain. The mathematical model is built up for the wind turbine with asynchronous wound-rotor generator. Results of the mathematical simulations showed that variations of the control angle of the short-circuiting transistor enables to move the point of wind turbine’s operation on its power curve, i.e., to control the quantity of inverted power. Regularities of the reactive power circulation between generator of wind turbine and grid as well as diminishing of the flicker emissions phenomena can be determined more exactly by means of further researches. Ill. 6, bibl. 10 (in English, summaries in English, Russian and Lithuanian).